Correction to “Some New Zealand Polyclads (Platyhelminthes, Polycladida)” - Holleman, John J. (Zootaxa, 2007)
It has come to my attention that the name of the new polyclad genus, Aotearoa, described in Holleman (2007), is a homonym of Aotearoa Forster and Platnick (1984), a New Zealand spider genus.